The first submillimeter observation of CO in the stratosphere of Uranus - Cavalie, T; Moreno, R; Lellouch, E; Hartogh, P; Venot, O; Orton, G; Jarchow, C; Encrenaz, T; Selsis, F; Hersant, F; Fletcher, L (2014)
Context. Carbon monoxide (CO) has been detected in all giant planets and its origin is both internal and external in Jupiter and Neptune. Despite its first detection in Uranus a decade ago, the magnitude of its internal and external sources remains unconstrained. Aims. We targeted CO lines in Uranus in the submillimeter range to constrain its origin. Methods. We recorded the disk-averaged spectrum of Uranus with very high spectral resolution at the frequencies of CO rotational lines in the submillimeter range in 2011-2012. We used empirical and diffusion models of the atmosphere of Uranus to constrain the origin of CO. We also used a thermochemical model of its troposphere to derive an upper limit on the oxygen-to-hydrogen (O/H) ratio in the deep atmosphere of Uranus. Results. We have detected the CO(8-7) rotational line for the first time with Herschel-HIFI. Both empirical and diffusion models results show that CO has an external origin. An empirical profile in which CO is constant above the 100 mbar level with a mole fraction of 7.1-9.0 × 10-9, depending on the adopted stratospheric thermal structure, reproduces the data. Sporadic and steady source models cannot be differentiated with our data. Taking the internal source model upper limit of a mole fraction of 2.1 × 10 -9 we find, based on our thermochemical computations, that the deep O/H ratio of Uranus is less than 500 times solar. Conclusions. Our work shows that the average mole fraction of CO decreases from the stratosphere to the troposphere and thus strongly advocates for an external source of CO in Uranus. Photochemical modeling of oxygen species in the atmosphere of Uranus and more sensitive observations are needed to reveal the nature of the external source. © ESO, 2014.